THE INFLUENCE OF DIGITAL MARKETING ON ENTREPRENEURIAL INTEREST: A STUDY OF STUDENTS - Nizmah Ahmad Bahasoan; Budi Jaya Sugiarto (Consilium: Education and Counseling Journal, 2026)
The advancement of digital technology has made digital marketing an important competency in increasing students' entrepreneurial interest. This study aims to examine the effect of digital marketing learning on students' entrepreneurial interest in the Informatics Management Study Program. The study used a quantitative approach with a pre-experimental method through a One Group Pretest–Posttest Design. The sample size was 63 students determined using a total sampling technique. Data collection was carried out using an entrepreneurial interest questionnaire that had met the validity and reliability criteria, then analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the Paired Sample t-test with the help of IBM SPSS Statistics 26. The results showed that the average entrepreneurial interest increased from 68.79 in the pretest to 84.65 in the posttest. Based on the Paired Sample t-test, there was a significant difference between the scores before and after treatment (t = 17.43; p < 0.001). This finding confirms that digital marketing learning has a positive and significant effect on increasing students' entrepreneurial interest. Learning that combines digital marketing theory and practice can increase students' interest, confidence, courage in taking risks, and commitment to entrepreneurship.